Initiatives for revitalization of endangered languages in Southern Mexico - Córdova Hernández, Lorena (2015)
Mexico is a country with a broad linguistic and cultural diversity. Certainly this is due to their number of languages, their sociocultural groups, and their dialectal variation. All of these characteristics show certain degree of language shift. However, every language needs to begin taking different actions (at the political, institutional, methodological level) for reversing language shift. This article aims to show the development of the project Revitalization of Endangered Languages Projects in Southern Mexico, 2014. This project was proposed by the Office’s Language Policies Assistant Director, National Institute of Indigenous Languages (Mexico). Specifically, the scope in this article is to describe the background of this project and how the six local or communal sub-projects linked to it have started revitalizing endangered languages with high degree or a very high degree of vanishing, in Oaxaca and Chiapas , in Southern Mexico.